Designing an Early Fire Detection System for Smart Homes: An IoT Simulation Using Wokwi Integrated with the Blynk Application - Dhoni Setyanto; Julianti, Amelia (Lembaga Pengembangan Kinerja Dosen, 2025)
Fire is a disaster that carries serious consequences, both in terms of human casualties and material losses. Such incidents can occur in various locations, including offices, public facilities, forests, and especially residential areas. Technological advances, particularly the Internet of Things (IoT), present an opportunity to develop automated early fire detection systems. The objective of this study is to design an IoT-based residential fire detection system. The tools utilized in this research include the Blynk application, the Wokwi platform, and various sensors. Based on the results of the design process, simulation, and testing of the IoT-based residential early fire detection system conducted using an ESP32 microcontroller and the Blynk application, it can be concluded that the system is capable of effectively performing early detection of potential fire hazards. Integration with the Blynk application allows this system to be monitored and controlled remotely via smartphone. Through the Blynk dashboard, users can view real-time sensor data, receive hazard notifications, and manually control devices such as windows and water pumps. This feature enhances the system's flexibility in providing early warnings and reduces the risk of fire hazards in residential environments.